Predicting Chinese father involvement: Parental role beliefs, fathering self-efficacy and maternal gatekeeping - Liu, Yang; Haslam, Divna M.; Dittman, Cassandra K.; Guo, Mingchun; Morawska, Alina (Frontiers in Psychology, 2022)
Despite the well-established importance of positive father involvement for child adjustment, father involvement tends to be much lower compared to mother involvement. Furthermore, there are few empirical studies on Chinese fathers and their involvement in parenting. This study used survey methodology to examine the predictors of Chinese father involvement with their preschoolers. The sample consisted of 609 Chinese parent dyads in Mainland China. Results showed that fathering self-efficacy and their beliefs about parental roles directly predicted father involvement in parenting. Maternal gate-opening had both direct and indirect associations with father involvement via fathers’ beliefs and fathering self-efficacy. Maternal gate-closing was not associated with father involvement. The findings suggest that fathers’ beliefs about parental roles, fathering self-efficacy, and maternal gate-opening are likely to play an important role in facilitating father involvement with their children. Family interventions and programs could target these modifiable factors to facilitate father involvement in Mainland China.